2001
DOI: 10.1016/s0378-1097(01)00034-9
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of calcium influx across the plasma membrane depends upon the initial rise of cytosolic calcium with activation of IP3 in rat enterocytes by heat-stable enterotoxin of Vibrio cholerae non-O1

Abstract: In response to heat-stable enterotoxin of Vibrio cholerae non-O1, the initial rise of cytosolic 2 entry to the cell as assessed by Mn 2 quenching of fura-2 fluorescence which suggested that calcium influx across the plasma membrane depends upon initial rise of this bivalent cation that maintained the sustained phase of [Ca 2 ]i response. Addition of toxin to the fura-2-loaded cells, preincubated with lanthanum chloride, resulted in reduction of [Ca 2 ]i level with a short duration of irregular sustained phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…2 The recently described cholix toxin, secreted by non-O1 strains, possesses ADP-ribose transferase activity against ribosomal eukaryotic elongation factor. 3 V. cholerae ElTor haemolysin (HlyA) is another important toxin secreted by most V. cholerae O1 and non-O1 strains.…”
mentioning
confidence: 99%
“…2 The recently described cholix toxin, secreted by non-O1 strains, possesses ADP-ribose transferase activity against ribosomal eukaryotic elongation factor. 3 V. cholerae ElTor haemolysin (HlyA) is another important toxin secreted by most V. cholerae O1 and non-O1 strains.…”
mentioning
confidence: 99%
“…Previously, we demonstrated that in the presence of AVP, which signals via Gq, SRIF increased [Ca 2 *} leading to insulin secretion in HIT-T15 cells [21,22]. Our findings suggested that the mechanism by which SRIF signals be through Gi/Go, and involve the phospholipase C pathway and mainly Ca 2 * release from the endoplasmic reticulum.…”
Section: Introductionsupporting
confidence: 50%
“…Studies in COS-1 cells provide further support for the Py dimer mediation of the cross-talk between the Gq-and Gi-coupled receptors [23]. Enhancement of Gq-dependent signals by Gi-coupled receptors in COS-7 cells requires an activated PLC-p and is mediated by the Py dimer [21]. In addition, activation of Gi/Go-coupled receptors has been shown to enhance the inositol phosphate signals generated by Gq-coupled receptors [28,29].…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Measurement of inositol phosphates followed modified procedures from a published report (Hoque et al, 2001). Cells were labeled with 20 Ci/ml of myo-[2-3 H]inositol at 37°C for 90 min, by which time the incorporation of 3 H into inositol lipids had reached a plateau (Hoque et al, 2001).…”
Section: Methodsmentioning
confidence: 99%